Formation of Tertiary Interactions during rRNA GTPase Center Folding. Issue 17 (28th August 2015) - Rau, Michael J.; Welty, Robb; Tom Stump, W.; Hall, Kathleen B.
Abstract: The 60-nt GTPase center (GAC) of 23S rRNA has a phylogenetically conserved secondary structure with two hairpin loops and a 3-way junction. It folds into an intricate tertiary structure upon addition of Mg 2 + ions, which is stabilized by the L11 protein in cocrystal structures. Here, we monitor the kinetics of its tertiary folding and Mg 2 + -dependent intermediate states by observing selected nucleobases that contribute specific interactions to the GAC tertiary structure in the cocrystals. The fluorescent nucleobase 2-aminopurine replaced three individual adenines, two of which make long-range stacking interactions and one that also forms hydrogen bonds. Each site reveals a unique response to Mg 2 + addition and temperature, reflecting its environmental change from secondary to tertiary structure. Stopped-flow fluorescence experiments revealed that kinetics of tertiary structure formation upon addition of MgCl2 are also site specific, with local conformational changes occurring from 5 ms to 4 s and with global folding from 1 to 5 s. Site-specific substitution with 15 N-nucleobases allowed observation of stable hydrogen bond formation by NMR experiments. Equilibrium titration experiments indicate that a stable folding intermediate is present at stoichiometric concentrations of Mg 2 + and suggest that there are two initial sites of Mg 2 + ion association. Graphical abstract: Highlights: The rugged landscape of RNA folding is explored here for a conserved 60-nt rRNA fragment from the perspective of individual nucleobases. Global folding of the GTPase center RNA is Mg 2 + dependent, but observing individual structural elements (hairpin, internal bulge, and hinge) shows a hierarchy of Mg 2 + -dependent structural changes. Kinetics of tertiary structure formation are not two-state but rather are a culmination of multiple conformational changes within the RNA on timescales ranging from < 1 ms to 4 s. The investigation of this RNA structural transition by monitoring individual nucleobases reveals their dynamic conformational changes before, during, and after the final tertiary structure has formed.